Evaluation of immediate and long-term results of treatment of post-radiation injuries of the rectum - Z. I. Teryushkova; A. V. Vazhenin; V. S. Vasilyev; S. A. Vasilyev; V. M. Timerbulatov (Амбулаторная хирургия)
Introduction. Treatment of post-radiation damage to the rectum is a complex medical problem. The search for new methods of treatment for this category of patients based on modern achievements in regenerative surgery is urgent.The aim of the study was to evaluate the immediate and long-term results of treatment of post-radiation lesions of the rectum using microfat grafting.Materials and methods. The study involved 66 patients — women aged 28 to 83 years inclusive with complications of radiation therapy (rectovaginal fistulas, radiation proctitis, radiation ulcers).Results and discussion. After the treatment, there is a tendency to improve the condition. So, if before the procedure the average sizes of fistulas and ulcers were 1.67 ± 0.54 cm in diameter, then after 3 months these indicators were 1.39 ± 0.54, and after 6 months — 1.1 ± 0.56 cm Complete epithelialization of the defect was observed in all patients. The period for which it was possible to achieve complete epithelialization varies from 6 months to 2 years. On average, to achieve complete epithelialization of post-radiation damage to the rectum, most patients required 3 injections of autologous adipose tissue. Also, all patients showed an improvement in elastometry indices over time. As a result of treatment, there is a tendency to improve the quality of life of patients.Conclutions. The study allows us to conclude about the effectiveness of the treatment, as well as that in the long term, the treatment will also be effective, the likelihood of relapse is minimal.